Pengaruh Konten Pemasaran, Media Sosial, Dan Brand Awareness Terhadap Keputusan Pembelian Produk Skincare: Studi Kasus Toko Meccacu - Putri, Anggun Eva Ardita; Basalamah, Muhammad Ridwan; Utama, Satria Putra (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the influence of Marketing Content, Social Media and Brand Awareness on Consumer Purchasing Decisions at the Meccacu Skincare Store. The research used is quantitative research with a population of consumers who have purchased skincare at the meccacu skincare store. Data processing is used using multiple linear regression analysis with the help of the SPSS (Statistical Package For Social Sciences) application. The results of this study indicate that marketing content does not have a significant effect on purchasing decisions, while social media and Brand awareness have a significant effect on purchasing decisions. Keywords: Marketing Content, Social Media, Brand Awareness, Consumer Purchasing Decisions